Rice (Oryza sativa L.) productivity, profitability, nutrient uptake and energetics under different nutrient management and rice establishment methods in rice-groundnut cropping system - Samant, TK; Garnayak, LM; Paikaray, RK; Mishra, PJ; Rath , BS (ORYZA-An International Journal of Rice, 2023)
A field experiment was conducted during 2019-20 and 2020-21 to study the effect of nutrient management and rice establishment methods on rice productivity, profitability, nutrient uptake and energetics in rice-groundnut cropping system in coastal Odisha. The experiment was laid out in factorial randomised block design during the Kharif and in split-plot design during the Rabi seasons with three replications. Six treatment combinations comprising of two rice establishment methods viz., direct seeded rice (DSR) and transplanted rice (TPR) and three nutrient management practices, viz., inorganic source, organic source and integrated nutrient management (INM) to rice during kharif were allotted to the main-plots. Three nutrient management practices to groundnut viz., 75% soil test based inorganic fertilizers (STBF), 100% STBF (inorganic) and INM during rabi were allotted to the sub-plots. The results of the study revealed that TPR resulted in 3.3% higher grain yield (5.65 t ha-1) than DSR. TPR also fetched the higher mean cost of cultivation (Rs. 77, 816 ha-1) and gross returns (Rs. 1, 12, 353 ha-1) while DSR recorded more net returns (Rs. 39, 121 ha-1) and benefit cost ratio (1.68). Transplanting increased uptake of nutrients by rice crop to the maximum of 99.4 kg N, 27.9 kg P and 107.3 kg K ha-1 as compared to DSR. TPR recorded the higher energy output (1, 48, 205 MJ ha-1), energy ratio (18.0) and energy productivity (0.69 kg MJ-1) than DSR. INM exhibited the highest mean grain (6.06 t ha-1) and straw yields (7.09 t ha-1), while the organic management showed at par of these values. The INM practice also fetched 50, 781 ha-1 and 7,470 ha-1 higher net returns and 0.84 and 0.04 higher benefit: cost ratio over organic practice and inorganic nutrition, respectively. The INM practice in rice crop resulted in the maximum N, P and K uptake. But, the inorganic and organic practice in isolation have similar uptake of nutrients by the crop in accordance with their almost similar yields. The minimum energy for raising rice crop was spent in organic practice, which generated maximum energy ratio (23.4) and energy productivity (0.87 kg MJ-1) followed by INM and inorganic practice. Thus, transplanting method of rice establishment with INM approach is a viable management practice for improving productivity, profitability, nutrient uptake and energy efficiency of rice in rice-groundnut cropping system in coastal Odisha.